Dimensions of IFRS transition roadmap's information content in LDCs: A case of Nigeria - Isa, Muhammad Aminu (Elsevier Ltd., 2014)
This paper assesses the dimensions of IFRS transition roadmap information content and its adequacy in guiding IFRS transition in Nigeria.Data were generated through self-administered questionnaire on 140 accountants that yielded 75.71% usable responses. Descriptive statistics and regression were used for the data analysis.It is discovered that the information content of the roadmap is not inclusive and inadequate to drive the transition to a successful implementation of IFRS.The information dimensions on education and awareness creation are not significantly contained in the roadmap.This adversely affects stakeholders’ effective planning and establishment mediating measures to ensure successful transition.